1998
DOI: 10.1242/jeb.201.4.487
|View full text |Cite
|
Sign up to set email alerts
|

How Body Size Affects Middle-Ear Structure and Function and Auditory Sensitivity in Gekkonoid Lizards

Abstract: Gekkonoid lizards increase in body size throughout life, and the present study investigates whether changes in auditory function accompany these increases. Middle-ear structures in four groups of animals, adults and juveniles of two gekkonoid species (Eublepharis macularius and Oedura marmorata), were examined. Tympanic membrane velocity and phase were also measured in all four groups. An indication of peripheral auditory function was obtained for each group by measuring compound action potentials (CAPs) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…These values are within the lower limit of those reported for other lizard species at different stimulus levels (e.g., between 0.2 and 6.9 mm/s; dB SPL: 100, Saunders et al, 2000; Werner et al, 2002; dB SPL: 94, Christensen‐Dalsgaard & Manley, 2005; dB SPL: 70, Han & Young, 2018). We cannot rule out, however, that higher velocities could have been recorded for these populations if the laser beam had been aimed at locations other than the insertion point of the extracolumella, considering that the eardrum stiffness varies across its surface (Han & Young, 2018; Werner et al, 1998) and that the eardrum exhibits frequency‐dependent vibration modes (Bergevin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These values are within the lower limit of those reported for other lizard species at different stimulus levels (e.g., between 0.2 and 6.9 mm/s; dB SPL: 100, Saunders et al, 2000; Werner et al, 2002; dB SPL: 94, Christensen‐Dalsgaard & Manley, 2005; dB SPL: 70, Han & Young, 2018). We cannot rule out, however, that higher velocities could have been recorded for these populations if the laser beam had been aimed at locations other than the insertion point of the extracolumella, considering that the eardrum stiffness varies across its surface (Han & Young, 2018; Werner et al, 1998) and that the eardrum exhibits frequency‐dependent vibration modes (Bergevin et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that a possible increase in middle ear volume may increase the permeability of lower frequencies by reducing the stiffness of the air in this cavity (Relkin 1988). In addition, increased body size has been associated with increases in the size of middle ear structures such as the eardrum, ossicles, and base of the stapes in animal models (Werner et al 1998; Werner & Igić 2002). An increase in mass can disrupt the transmission of high frequencies through the middle ear (Werner & Igić 2002).…”
Section: Discussionmentioning
confidence: 99%